2018
DOI: 10.26740/jpps.v7n2.p1513-1518
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPMENT OF THE GUIDED INQUIRY STUDENT WORKSHEET FOR BIOLOGY GRADE 11th SENIOR HIGH SCHOOL

Abstract: The purpose of this study is produced Students’ Worksheet (LKS) which valid, practice, and effective to support the learning biology materials using a guided inquiry model. The development of worksheets is using ADDIE (analyze, design, develop, implement, and evaluate) models and being implemented in XI Grade senior high of Trensains Tebuireng Jombang on odd semester of 2016/2017 academic year with the One-group pretest-posttest design. The validity of the worksheet is measured from consistency (construct vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…Critical thinking skills and ICT Literacy that have not been accommodated properly can be overcome with guided inquiry-based e-modules. The components of the guided inquiry model are orientation, problem formulation, hypothesis formulation, data collection, hypothesis testing, and conclusion formulation (Aulia et al, 2018;Windiastuti et al, 2018;Zammiluni et al, 2018). The six components of the guided inquiry model can train and facilitate indicators on ICT literacy critical thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…Critical thinking skills and ICT Literacy that have not been accommodated properly can be overcome with guided inquiry-based e-modules. The components of the guided inquiry model are orientation, problem formulation, hypothesis formulation, data collection, hypothesis testing, and conclusion formulation (Aulia et al, 2018;Windiastuti et al, 2018;Zammiluni et al, 2018). The six components of the guided inquiry model can train and facilitate indicators on ICT literacy critical thinking skills.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it concluded that the guided inquiry-based physics learning materials are valid, practical, and effective for use in teaching and learning and can facilitate the development of science process skills in junior high school students. (Windiastuti et al, 2018) stated that the development of The Guided Inquiry student worksheet for Biology 11 th Grade Senior High School is legitimate, practical, and successful.…”
Section: Resultsmentioning
confidence: 99%
“…The data analysis of the questionnaire of teacher and student's responses was measured using the Guttman scale. Measuring scale with this type, will get a firm answer, namely "Yes" or "No" The results of the percentage scores were then converted to feasible (0% -20%), less feasible (21%-40%), enough (41% -60%), feasible (61% -80%), and very decent (81% -100%) (Windiastuti et al, 2018).…”
Section: Discussionmentioning
confidence: 99%